A Load Impedance Function for the Simultaneous Maximum Voltage and Maximum Power (University of Khartoum Engineering Journal, 2022)
Results of a load impedance function that will present conditions for the simultaneous occurrence ofmaximum voltage and maximum power at the terminals of a linear transducer circuit are given. The statement isbased on algebraic solution to the problem of maximum power in voltage- and resistance-constrained radialtransmission lines. As a result, it is shown that the load impedance conditions for maximum power with conjugatematching and Brainerd’s maximum load voltage condition are embodied in the generalized load impedancefunction as the upper and lower limiting states of maximum received power; and that a purely resistive state forthis function will determine the limit to stable power transfer. In addition, a case for the optimum transmissionreactance that will enable extraction of maximum voltage at the maximum powers of conjugate impedancematching is demonstrated